2020
DOI: 10.13106/jbees.2020.vol10.no1.7
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Remittances, Banking Sector Development and Private Sector Investment

Abstract: Purpose-This study seeks to investigate the impact of foreign remittances on private sector investment and the moderating role of banking sector development in Sub-Saharan African Countries. Research design, data, and methodology-The study has used a sample of 15 Sub-Saharan African countries and data for the years 1986 -2017. Data was obtained from the World Bank Development Indicator (WDI) Database. Panel data diagnostic tests were conducted to ascertain the suitability of the data for regression analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…The findings contradict several studies that found the institutional quality to be a complement to remittance in the development process (Catrinescu et al. , 2009; Adams and Klobodu, 2016 Githaiga, 2020). The discrepancy in findings could be explained by the fact that the moderating effect of institutions on the remittances-investment and remittances-growth nexuses differed and the majority of the existing literature employed growth as the dependent variable.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The findings contradict several studies that found the institutional quality to be a complement to remittance in the development process (Catrinescu et al. , 2009; Adams and Klobodu, 2016 Githaiga, 2020). The discrepancy in findings could be explained by the fact that the moderating effect of institutions on the remittances-investment and remittances-growth nexuses differed and the majority of the existing literature employed growth as the dependent variable.…”
Section: Resultscontrasting
confidence: 99%
“…As a result, this paper aims to examine the role of institutional quality in moderating the remittances-investment nexus. Our study is similar to Adams and Klobodu (2016) and Githaiga (2020) but differs by choosing investment as the dependent variable and by including nonfinancial variables.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential contribution that foreign remittances can make to investment, economic equality, reductive feelings of deprivation, poverty reduction and growth is widely accepted and documented in academic and policy circle (World Bank 2014 ; Fagerheim 2015 ; Jongwanich 2017 ; Sayantan 2017 ), and thus improving inflow of foreign remittances to nations across the world has become an issue of increasing focus for government and policy makers. This is more important in developing countries where foreign remittances far surpass development aid, forms an important addition to domestic income and instrumental to investment dynamics and poverty reduction (Akobeng 2016 ; Kelvin 2017 ; GiThaiga 2020 ; Shah et al 2021 ). But the empirical link between foreign remittances and reductive or weak growth, increased feelings of economic inequality and deprivation has also been established in the academic literature.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign capital inflows are remittances from foreign nations transferred to developing countries majorly by members of that country living abroad Githaiga (2020). Foreign capital inflows are major forms of resource transfer from the developed to the developing countries where they are usually found to be more productive (Williams, 2016;Sobiech, 2019;ERP, 2006).…”
Section: Introductionmentioning
confidence: 99%